2017
DOI: 10.1039/c6nj03709g
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene glycol derivatization of the non-active ion in active pharmaceutical ingredient ionic liquids enhances transdermal delivery

Abstract: Introducing PEGylated moieties into the counterion structure of API–ILs can significantly enhance the transport through a membrane without a solvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…More specifically, Vincent et al [80] and Langgartner, J. et al [81] similarly demonstrated that transport across biological membranes bearing a highly polar anionic framework can be facilitated if the APIs are paired with lipophilic ammonium ions that act as phase transfer agents. Additionally, Rogers et al [82] recently demonstrated on synthetic membrane models that API-OSILs that contain lipophilic cations, preferably with established hydrogen bonds, exhibit an increased membrane transport as compared to API-OSILs with weaker electrostatic interactions or even traditional halide or metal salts. Finally, it is important to note that both hydrophobic and hydrophilic ionic liquids have been recently studied as penetration enhancers [16,20,83,84].…”
Section: Studies On Resistant Bacteriamentioning
confidence: 99%
“…More specifically, Vincent et al [80] and Langgartner, J. et al [81] similarly demonstrated that transport across biological membranes bearing a highly polar anionic framework can be facilitated if the APIs are paired with lipophilic ammonium ions that act as phase transfer agents. Additionally, Rogers et al [82] recently demonstrated on synthetic membrane models that API-OSILs that contain lipophilic cations, preferably with established hydrogen bonds, exhibit an increased membrane transport as compared to API-OSILs with weaker electrostatic interactions or even traditional halide or metal salts. Finally, it is important to note that both hydrophobic and hydrophilic ionic liquids have been recently studied as penetration enhancers [16,20,83,84].…”
Section: Studies On Resistant Bacteriamentioning
confidence: 99%
“…This strategy was first investigated by Megwa et al [61], who combined the salicylate anion with alkylammonium and quaternary ammonium cations to improve the skin permeation of the API. After this pioneering work, other studies attempted to improve the permeation of salicylates across membranes, being reported as new salicylate-based ILs [62] and ILs with derivatives of poly(ethylene glycol) [63]. The selection of more biocompatible cations, such as amino acids, has been also considered for this purpose [64].…”
Section: Ils As Permeation Enhancers and Microemulsion Components For Drug Deliverymentioning
confidence: 99%
“…Recently, a group at McGill University described the development of ILs to improve the delivery of poorly soluble drugs through the skin. Zavgorodnya et al studied the effects of various counterions on the membrane permeability of salicylate-based APIs-ILs [43]. Specifically, they paired three counterions (choline, tributylammonium, and triethylene glycol monomethyl ether tributylammonium) with a salicylate anion to generate three different API-ILs and assessed their impact on transdermal diffusion using a silicone membrane as a skin mimic.…”
Section: Chemical Permeation Enhancer-based Systemsmentioning
confidence: 99%